RANDOMIZED STUDY: PROPOFOL VERSUS FENTANYL-MIDAZOLAM COMBINATION FOR CONSCIOUS SEDATION DURING FIBREOPTIC NASOTRACHEAL INTUBATION - Manisha; yadav, Kavita; Sinha, Abhinav (Student’s Journal of Health Research Africa, 2024)
Background The ideal characteristics of the sedative and analgesic that is used for awake fiberoptic intubation are that it should be easily titrable, that it should act rapidly, that it should maintain hemodynamic stability, that it should provide sufficient amnesia, and that it should have a short-acting time because the manipulation of the airway is only required until the intubation is finished. Currently, fentanyl and midazolam are used; propofol also fits the characteristics. This study aims to determine the efficacy and safety of both agents in the conduction of awake fiberoptic intubation. Method This study was a prospective randomized study. There were a total of 25 participants in the study. All of them underwent a pre-anesthetic assessment. The patients were divided into two groups. The first group received propofol as their sedating agent and the second group received fentanyl and midazolam combination as their sedating agent. The intubation period, sedation score, intubation score, hemodynamic vitals, oxygen saturation, degree of amnesia, and degree of global acceptance were recorded. Results Both propofol and the fentanyl-midazolam combination were effective for sedation during fiberoptic intubation. Propofol had a slightly higher sedation score at 2 minutes (mean: 13.3 vs. 15.5, p < 0.05), but both groups reached similar sedation levels at 6 minutes (score: 16). Intubation scores showed no significant differences between groups (p > 0.05). Propofol provided better hemodynamic stability, with lower systolic blood pressure during stage 2 (p < 0.05). Oxygen saturation remained stable in both groups. Complete amnesia was achieved in 75% of the propofol group and 85% of the fentanyl-midazolam group, with similar global acceptance ratings (75% vs. 85%). Conclusion Propofol alone is suitable for awake fiber optic insertion for artificial ventilation. Recommendation Propofol should be considered as a sedative agent for the performance of fiber optic insertion for artificial ventilation.